Forecasting crop yields under climate oscillations: Implications for agricultural planning and resilience - Devadharshini, S; Sathyamoorthy, N K (Plant Science Today, 2026)
Climate oscillations such as the El Niño-Southern Oscillation (ENSO), Indian Ocean Dipole (IOD) and North Atlantic Oscillation (NAO) significantly influence global weather variability, posing challenges to agricultural productivity and food security. Their impacts−ranging from altered rainfall patterns to temperature extremes−disrupt crop growth, especially in rainfed systems. Understanding these oscillations is vital for enhancing yield prediction and informing adaptive agricultural planning. This review synthesizes mechanistic insights and empirical findings from peer-reviewed literature on the influence of ENSO, IOD and NAO on crop yields across major agro-climatic zones. It also evaluates predictive tools, including statistical models, dynamic crop simulations and AI-driven forecasting systems. Crop-specific vulnerabilities and regional disparities in oscillation impacts were systematically analyzed to assess adaptation needs. Findings reveal that ENSO, IOD and NAO generate region-specific yield anomalies by modulating soil moisture, evapotranspiration and phenological development. Crops such as rice, maize and wheat exhibit heightened sensitivity during key growth stages under oscillation-driven stressors. Modern forecasting models incorporating oscillation indices improve predictive accuracy and provide early warnings for yield variability. However, gaps remain in translating forecasts into actionable farm-level decisions, especially in resource-limited regions. To build agricultural resilience, integrating oscillation-based forecasts into local advisory services, promoting climate-smart practices and adopting inclusive, region-specific adaptation strategies are essential. Bridging science-policy gaps and strengthening climate services will support anticipatory planning and safeguard food systems under increasing climate variability.